TOMM40 and APOE Gene Expression and Cognitive Decline in Japanese Alzheimer's Disease Subjects - Mise, Ayano; Yoshino, Yuta; Yamazaki, Kiyohiro; Ozaki, Yuki; Sao, Tomoko; Yoshida, Taku; Mori, Takaaki; Mori, Yoko; Ochi, Shinichiro; Iga, Jun-Ichi; Ueno, Shu-Ichi (Journal of Alzheimer's disease, 2017)
TOMM40 is located on chromosome 19, is in linkage disequilibrium with apolipoprotein E (APOE), andis reported in several genome-wide association studies to be associated with Alzheimer's disease (AD). Assess APOE and TOM40 and mitochondrial genes as blood biomarkers for AD. We examined TOMM40, PTEN-induced putative kinase 1 (PINK1), Parkin RBR E3 ubiquitin protein ligase (PARK2), and APOE mRNA expression in relation to the methylation rates of CpG sites in the upstream region of TOMM40exon 1 in peripheral leukocytes and TOMM40523 polyT genotypes in 60 AD and age- and sex-matched control subjects. TOMM40 mRNA expression was significantly lower in AD subjects (0.87±0.18 versus 1.0±0.23, p = 0.005), and PINK1 mRNA expression was higher in AD subjects (1.5±0.61 versus 1.0±0.52, p < 0.001). TOMM40 mRNA expression was significantly correlated with the Mini-Mental State Examination total score (r = 0.290, p = 0.027). There was no expressional change in peripheral APOE mRNA in either AD or control subjects (p = 0.32). Methylation rates in the upstream region of TOMM40exon 1 were not different between AD and control subjects (average rate: 1.37±0.99 versus 1.39±1.20, p = 0.885), and TOMM40523 polyT genotypes were also not different between AD and control subjects (p = 0.67). TOMM40 mRNA expression was lower in AD subjects and was correlated with cognitive decline. Significant changes in both TOMM40 and PINK1 mRNA may be related to mitochondrial dysfunction.